Case report: Emphysematous cystitis due to Escherichia coli infection with the extension of gas into multiple locations in two non-diabetic dogs: a computed tomographic diagnosis and successful management - Lee, Eun-Ji; Lee, Jeong-Min; Kim, Jin-Young; Hwang, Tae-Sung; Song, Kun-Ho; Song, Joong-Hyun (Frontiers in Veterinary Science, 2023)
Emphysematous cystitis is an extremely rare, complicated urinary tract infection with the presence of gas in the bladder wall and lumen caused by gas-producing bacterial infections. A 7-year-old spayed female Pomeranian dog presented with a 3-day history of hematuria and pollakiuria (case one), and a 9-year-old spayed female Jindo dog presented with a 4-day history of intermittent hematuria (case two). Imaging modalities including radiography, ultrasonography, and computed tomography, and bacterial culture test were used for diagnosis. Emphysematous cystitis due to Escherichia coli infection with the extension of gas into multiple locations was identified in both cases. Based on the results of antibiotic susceptibility testing, systemic antibiotics were initiated. Both animals had an excellent response to antibiotic treatment, and the clinical signs of gas collection completely resolved within approximately 1 month after treatment initiation. This response was sustained without recurrence in the follow up period. This case report describes clinical details of extremely rare canine cases of emphysematous cystitis with the extension of gas into multiple locations and evaluates the clinical efficacy of antibiotic therapy.